take the coefficient of x and half it, then square it
so that is 3/2, squaring it we have 9/4
now add that to both sides
x^2 + 3x + 9/4 = 4 + 9/4
now the left hand side is a perfect square
(x+ 3/2)^2 = 25 / 4
taking the square root of both sides we have
x + 3/2= +- 5/2
so x = (-3+-5)/2
x=-4 or x = 1
2007-05-28 15:52:53
·
answer #1
·
answered by TENBONG 3
·
1⤊
0⤋
You must add a constant c that will make x²+3x+c factorable into the square of a binomial. To find this constant, consider the formula for square of a sum:
(a+b)²=a²+2ab+b²
Now x=a, and you must figure out b:
2ab=3x
2b=3
b=3/2
Therefore, you must add (3/2)²=9/4 to both sides of your equation. This will turn the left side into the square of a binomial:
x²+3x+9/4=4+9/4
(x+3/2)²=25/4
Now take the square root of both sides:
x+3/2=±5/2
x=-3/2±5/2
x=1 or x=-4
Check:
1²+3(1)=4
1+3=4
(-4)²+3(-4)=4
16-12=4
2007-05-28 22:57:29
·
answer #2
·
answered by Chris S 5
·
0⤊
0⤋
It's hard to explain here, but I'll try.
(If there was a leading coefficient, you would divide it out before this stage.)
Put in a blank.
(x^2 + 3x + ___ ) = 4
In the blank: (b/2)^2 [FYI: b is the coefficient of the second term in the trinomial]
Whatever you put in the blank, you have to add to the other side to keep it balanced. (If there were a leading coefficient that you had divided out, you would multiply, then add that number to other side.)
(x^2 + 3x + (9/4)) = 4 + 9/4
(x + __ )^2 = 16/4 + 9/4
The sign that goes in the binomial is the same as the sign on b.
In this blank: b/2 from your first trinomial
(x + (3/2))^2 = 25/4
Solve for x. Remember, since it's a square root, you have to do plus or minus.
x + 3/2 = (+/-)5/2
x = 5/2 - 3/2 = 2/2 = 1
x = -5/2 - 3/2 = -8/2 = -4
x = 1 or -4
2007-05-28 22:55:25
·
answer #3
·
answered by its_victoria08 6
·
0⤊
0⤋
To find the constant value to add to both sides, divide the linear term by 2 and square it.
(3/2)^2 = 9/4.
Add 9/4 to both sides:
x^2 + 3x + 9/4 = 4+9/4
Factor the quadratic as a perfect square binomial:
(x+3/2)^2 = 25/4
Take the square root of both sides
x+3/2 = +/-sqrt(25/4)
x + 3/2 = +/- 5/2
Solve for x:
x = 1 or -4.
2007-05-28 22:54:58
·
answer #4
·
answered by Anonymous
·
1⤊
0⤋
x² + 3x + 9/4 = 4 + 9/4
(x + 3/2)² = 25/4
x + 3/2 = ± 5/2
x = - 3/2 ± 5/2
x = 1 , x = - 4
2007-05-29 05:59:45
·
answer #5
·
answered by Como 7
·
0⤊
0⤋
Take half of 3x and square it (3/2)^2
x^2+3x+9/4=4+9/4
(x+3/2)^2=25/4
sq.rt (x+3/2)^2=sq.rt25/4
x+3/2=+(-)5/2
x=-3/2+5/2 or -3/2-5/2
x=1 or x=-4
2007-05-28 22:58:31
·
answer #6
·
answered by mr. math 2
·
0⤊
0⤋